(untitled) (Global Journal of Science Frontier Research, 2020)
Transplant quality of Echinops giganteus depends on factors like: microclimate parameter, substrate, plant nutrition, and others. The growth stage is also an important index of its quality. The objective of this research was to determine the effect of transplants’ growth stage on the mortality rate and quality of Echinops giganteus seedlings after transplant. The research work was carried out on nursery beds at the Research Institute of Agricultural Development (RIAD). The investigated transplant growth stages were seedling height, number of leaves and seedling age. Data collection began one month after the transplant, and the observations were done every week for eight weeks. The growth stages of Echinops giganteus transplants had no significant effect on the average yield, but the mortality rates were greatly affected by the transplant growth stages. From the results of this experiment, mortality rates were low when seedlings were transplanted with two leaves (17%) and at 12 cm (22%). When seedlings of Echinops giganteus were transplanted at an earlier growth stage, the mortality rates were lower than when they were transplanted at an older growth stage.